Women in the boardroom and their impact on governance and performance☆ - Adams, Renée B.; Ferreira, Daniel (Journal of Financial Economics, 2009)
We show that female directors have a significant impact on board inputs and firm outcomes. In a sample of US firms, we find that female directors have better attendance records than male directors, male directors have fewer attendance problems the more gender-diverse the board is, and women are more likely to join monitoring committees. These results suggest that gender-diverse boards allocate more effort to monitoring. Accordingly, we find that chief executive officer turnover is more sensitive to stock performance and directors receive more equity-based compensation in firms with more gender-diverse boards. However, the average effect of gender diversity on firm performance is negative. This negative effect is driven by companies with fewer takeover defenses. Our results suggest that mandating gender quotas for directors can reduce firm value for well-governed firms.